Transparent, metal-free PEDOT:PSS neural interfaces for simultaneous recording of low-noise electrophysiology and artifact-free two-photon imaging - Hyun Woo Kim; Jiwon Kim; Jong Youl Kim; Kyubeen Kim; Ju Young Lee; Taemin Kim; Shinil Cho; Jong Bin An; Hyun Jae Kim; Lulu Sun; Sunghoon Lee; Kenjiro Fukuda; et al. (Nature Communications)
Abstract Simultaneous two-photon imaging and electrophysiological recordings offer considerable potential for advancing neurological research and therapies. However, traditional metal-based neural interfaces suffer from photoelectric artifacts, while existing transparent implants rely on opaque interconnect lines to address conductivity limitations. Herein, we developed an optically transparent poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) neural electrode array with transparent electrodes and interconnect lines. Through a formamide, phosphoric acid, and ethylene glycol treatment, the metal-free PEDOT:PSS array achieved an impedance of 45.8 kΩ (at 1 kHz) even with a 20 × 20 µm² size. This advanced performance surpasses previous metal-free transparent neural interfaces and facilitates precise electrophysiological recordings, including extracellular action potentials and low-noise local field potentials. In vivo experiments demonstrated artifact-free two-photon imaging and reliable neural signal acquisition, while biocompatibility tests confirmed negligible cytotoxicity or immune responses. The developed metal-free PEDOT:PSS array provides a robust platform for neural recording and bioimaging, representing an advancement in transparent neural interface technology and integrated optical modalities.